Caste system, untouchability, and the depressed - Kotani, H, Ed.; Kotani, Hiroyuki (New Delhi : Manohar Publishers & Distributors, 1997)
On India; articles selected from a Japanese text and translated into English.
Keywords: Caste; Dalits